Perancangan Sistem Informasi Rekam Medis di Puskesmas Manggari Kuningan - Gifari Ahya Irawan; Otong Rukmana (Jurnal Riset Teknik Industri, 2024)
Abstract. The Community Health Center (Puskesmas) is one of the most important health service facilities in Indonesia. According to the Ministry of Health of the Republic of Indonesia (2004), the Puskesmas is a Regency/City Regional Technical Implementation Unit (UPTD) which is responsible for implementing Health development in a work area. The Manggari Health Center which is one of the health service centers in Kuningan Regency is one of the health agencies that is being developed Patient data collection and medical record archiving is an important thing that needs attention. Based on the results of observations and interviews conducted with Puskesmas employees, it was stated that treatment services at the Puskesmas in terms of patient data collection from patient registration to archiving patient medical records were still done manually. This means that everything is still written down on piles of paper and stored on storage shelves, so that when the puskesmas needs patient data, as well as visit reports, it takes quite a long time to find where the data is stored. Abstrak. Pusat Kesehatan Masyarakat (Puskesmas) merupakan salah satu sarana pelayanan kesehatan yang sangat penting di Indonesia. Berdasarkan Kemenkes RI (2004), Puskesmas merupakan Unit Pelaksanaan Teknis Daerah (UPTD) Kabupaten / Kota yang bertanggung jawab menyelenggarakan pembangunan Kesehatan di suatu wilayah kerja.Puskesmas Manggari yang menjadi salah satu pusat pelayanan kesehatan di Kabupaten Kuningan merupakan salah satu instansi kesehatan yang sedang dikembangkan. Pendataan pasien dan pengarsipan catatan medis merupakan suatu hal penting yang perlu diperhatikan. Berdasarkan hasil observasi dan wawancara yang diakukan dengan pegawai Puskesmas, menyebutkan bahwa pelayanan berobat di Puskesmas dalam hal pendataan pasien dari mulai pendaftaran pasien sampai pengarsipan catatan medis pasien masih dilakukan secara manual. Artinya semuanya masih ditulis pada tumpukan-tumpukan kertas dan di simpan pada rak-rak penyimpanan, sehingga ketika pihak puskesmas membutuhkan data-data pasien, dan juga laporan kunjungan, perlu waktu yang cukup lama untuk mencari dimana data tersebut disimpan.